Review of Psychosemantics, by Jerry Fodor - Dennett, Daniel C. (Tufts Archival Research Center, 2014)
Dennett, Daniel C. "Review of Psychosemantics, by Jerry Fodor." Journal of Philosophy 85 (July 1988): 384-389.